Recent Innovations, Modifications, and Evolution of ACC/AHA Clinical Practice Guidelines: An Update for Our Constituencies. Issue 17 (23rd April 2019) - Levine, Glenn N.; O'Gara, Patrick T.; Beckman, Joshua A.; Al-Khatib, Sana M.; Birtcher, Kim K.; Cigarroa, Joaquin E.; de las Fuentes, Lisa; Deswal, Anita; Fleisher, Lee A.; Gentile, Federico; Goldberger, Zachary D.; Hlatky, Mark A.; et al.
Abstract : Supplemental Digital Content is available in the text.